(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg Hf iUObg HVe GdUGO hSchf GdOGd, bhdg bO HGY faSg HCf cGf gfGc TNU GbfYg aj Cf jHYg Ydi TNU BNQ, bhdg Ch NOY aHjYs
(3BNQgG (B:s
(3BNQgG(B: (3hJhge EOQGL MGUd gPG GdJhge gh Cf gPg GdaQhV GdKdGKI eJSGhjI aj GdGTcGd djS HYVgG Chdi HGdGTcGd ef ZjQgG dCf cd efgG jecf GOQGLg JMJ Jcdja hGMO hgh GLJfH Yf GdMQGes
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs